Tinjauan Atas Pengisian Dan Pelaporan SPT Tahunan 1770 S Wajib Pajak Orang Pribadi Melalui E-Filling - Rosalia, Vanisa; Asfiya, Nurul; Efrianti, Desi; Wahyuni, Iis (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Implementaiton Annual Tax Return and E-Filing ________73 Submitted JANUARY 2024 Accepted APRIL 2024 JABKES Jurnal Aplikasi Bisnis Kesatuan Vol. 4 No. 1, 2024 page. 73-102 IBI Kesatuan ISSN 2807 – 6036 DOI: 10.37641/jabkes.v4i1.1898 The Directorate General of Taxes continues to provide innovations related to the online tax administration system in line with the times. The operation of the system is made simple, easy, and practical. This aims to assist taxpayers in facilitating the implementation of online tax administration. E-Filling is one of the online tax service systems whose operation uses a website to report individual tax returns annually. This tax service has been running for a dozen years, especially at the Ciawi Bogor Primary Tax Service Office. The purpose of the review is to find out how the procedure for filling and reporting the Annual SPT of Individual Taxpayers through e-Filling at the Ciawi Bogor Primary Tax Service Office, especially Form 1770 S, and what obstacles occur during the process of filling and reporting the Annual SPT. The results of the review that the filling and reporting of the Annual SPT 1770 S Individual Taxpayer through E-Filling at the Ciawi Bogor Primary Tax Service Office in the implementation of its activities has been running well and effectively. This activity can facilitate taxpayers who have difficulties or obstacles in filling and reporting their Annual SPT. These taxpayers will be guided by the e-Filling service starting from applying for an EFIN if they don't have one or forget it, then the process of registering a DJP Online account for those who have never registered, forgetting their password/email if any, then the process of filling out and reporting the Annual Tax Return until the tax return is sent and receiving Electronic Receipt Evidence sent by the online DJP email to the taxpayer's email. Keywords: Tax Administration, Annual Tax Return, e-Filling.